2018
DOI: 10.1111/jnc.14452
|View full text |Cite
|
Sign up to set email alerts
|

Sulfatide isoform pattern in cerebrospinal fluid discriminates progressive MS from relapsing‐remitting MS

Abstract: Multiple sclerosis (MS) is an inflammatory demyelinating disease of the central nervous system (CNS). Several biomarkers including proteins and lipids have been reported in MS cerebrospinal fluid (CSF), reflecting different aspects of the pathophysiology particularly of relapsing-remitting MS (RRMS). Sulfatide, abundant in the myelin sheath and a proposed target for autoimmune attack in MS, has been reported altered in MS CSF. Here, we investigated the potential of CSF sulfatide and its isoforms as biomarkers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 50 publications
(54 reference statements)
0
6
0
Order By: Relevance
“…Since vitamin K stimulates sulfatide biosynthesis in the brain, the vitamin K antagonist warfarin impairs brain sulfatide [ 41 ]. Sulfatide, on the other hand, may have a role in the pathogenesis of autoimmunity by acting as a possible ligand for L and P-selectin and up-regulating the expression of chemokine co-receptors (CXCR4) on neutrophils [ 42 ]. In an experimental investigation, sulfatide stimulates the replication of influenza A virus and hepatitis C virus (HCV) [ 43 , 44 ].…”
Section: Fenofibrate and Covid-19mentioning
confidence: 99%
“…Since vitamin K stimulates sulfatide biosynthesis in the brain, the vitamin K antagonist warfarin impairs brain sulfatide [ 41 ]. Sulfatide, on the other hand, may have a role in the pathogenesis of autoimmunity by acting as a possible ligand for L and P-selectin and up-regulating the expression of chemokine co-receptors (CXCR4) on neutrophils [ 42 ]. In an experimental investigation, sulfatide stimulates the replication of influenza A virus and hepatitis C virus (HCV) [ 43 , 44 ].…”
Section: Fenofibrate and Covid-19mentioning
confidence: 99%
“…In MS, metabolomics showed discrete metabolite profiles of CSF [92]. Other studies found the CSF metabolome to distinguish MS and NOSD [93], as well as between secondary progressive MS and relapsingremitting MS [94]. One can envision that the differential diagnosis of nervous system autoimmune diseases might be supported by a panel of proteins or metabolites in the future.…”
Section: Box 2 Analyzing Metabolism and Solutesmentioning
confidence: 99%
“…Through effects on protein localization, glycosphingolipids might play a role in the dysmyelination or demyelination processes observed in several pathologies. Indeed, various demyelinating diseases, including multiple sclerosis (MS), are associated with alteration of gangliosides and/or sulfatides (Novakova et al, 2018). Differences in the level and nature of sulfatides have been observed, especially in cerebrospinal fluid of patients with progressive MS compared with healthy do-nors or patients with relapsing-remitting MS (Novakova et al, 2018).…”
Section: Review Of Mcgonigal Et Almentioning
confidence: 99%
“…Indeed, various demyelinating diseases, including multiple sclerosis (MS), are associated with alteration of gangliosides and/or sulfatides (Novakova et al, 2018). Differences in the level and nature of sulfatides have been observed, especially in cerebrospinal fluid of patients with progressive MS compared with healthy do-nors or patients with relapsing-remitting MS (Novakova et al, 2018). Surprisingly, in addition to reporting a possible reduction of sulfatide in the normal-appearing white matter of MS patients, Marbois et al (2000) showed a significant alteration in the sulfatide species present in MS.…”
Section: Review Of Mcgonigal Et Almentioning
confidence: 99%